Are people inequality averse, and do they prefer redistribution by the state? : A revised version - Johannes Schwarze; Marco Härpfer (Institute for the Study of Labor (IZA), 2003)
We link life-satisfaction data to inequality of the pre- and post-government income distribution at the regional level, to estimate the degree of inequality aversion. Three different inequality measures are used. In addition, we investigate whether a reduction in inequality by the state increases individual well-being. We find only weak evidence that Germans are inequality averse. Inequality reduction by the state does not increase wellbeing. On the contrary, inequality reduction imposes an excess burden on middle-income earners. The paper uses data from the German Socio-economic Panel Study (GSOEP) from 1985 to 1998.
Keywords: I31; D63; D31; C23; 330; inequality aversion; redistribution; life satisfaction; panel data; Einkommensverteilung; Soziale Werte; Einkommensumverteilung; Lebensqualität; Schätzung; Deutschland; Lebenszufriedenheit